The Role of Leadership and Influence on Employee Performance in Digital Era - Dedi Iskamto (Universitas Pendidikan Nasional, 2020)
This research is a quantitative discretive research. According to Sugiono (2010), quantitative descriptions are research by drawing a conclusion from the data tabulated in the form of frequency distribution tables. The location of this research is at PT Mitra Beton Mandiri (MBM), Pekanbaru Riau City. The sample sample is 67 people. The results showed bbased on the total average value of the leadership recapitulation results, it is known that the respondent's response to the statement on the leadership variable is agree with the average value of 3.95%. From these data it can be seen that the leadership is good. Based on the average value of the performance recapitulation results, it is known that the respondent's response to the statement on the performance variable is in agreement with the average value of 4.00%. From these data it can be concluded that the employee's performance is good. Based on the results of the recapitulation of the leadership variable with the lowest average score for the tenth question with an average score of 3.83, which is for the achievement orientation indicator. Based on the results of the recapitulation of performance variables with the lowest average score for the eleventh question with an average score of 3.90, namely for the Communication indicator.